Evaluation of the use of chlorpromazine for agitation in pediatric patients - Rajwoana Ahmed, PharmD; Megan Maroney, PharmD, BCPP; Germin Fahim, PharmD, BCPS; Hoytin Lee Ghin, PharmD, BCPS; Andrew Scott Mathis, PharmD (American Association of Psychiatric Pharmacists, 2023)
Introduction: Chlorpromazine is a first-generation antipsychotic used for behavioral problems in pediatric patients. However, other therapies may demonstrate both improved outcomes and fewer side effects. Within our institution, chlorpromazine has been the standard medication used for treatment of pediatric agitation. The study objective was to evaluate the appropriateness of chlorpromazine use (including efficacy, appropriate dosing, drug interactions, and tolerability) to optimize the treatment of pediatric agitation. Methods: Data regarding drug interactions, patient behavior, dosing, and side effects was collected for each patient administered chlorpromazine from January 2019 through June 2019. Data were analyzed using descriptive statistics assessing the incidence of drug-drug interactions (DDIs), incidences of inefficacy, inappropriate dosing, and side effects. Results: A total of 70 patients and 130 administrations of oral or intramuscular chlorpromazine were evaluated. Of these administrations, 49 (38%) resulted in a DDI. Eighteen (14%) administrations were ineffective for managing symptoms of agitation. Eleven (8%) administrations were dosed inappropriately, and 46 (35%) administrations resulted in side effects possibly caused by chlorpromazine. Discussion: Results from this study demonstrate opportunities for improvement in patient care due to instances of drug interactions, inefficacy, inappropriate dosing, and side effects with the use of chlorpromazine.